Cost-effectiveness analysis of bariatric surgery for morbid obesity in Belgium. (3rd April 2018) - Borisenko, Oleg; Lukyanov, Vasily; Debergh, Isabelle; Dillemans, Bruno
Abstract: Aims: This study presents the cost-effectiveness analysis of bariatric surgery in Belgium from a third-party payer perspective for a lifetime and 10-year horizon. Materials and methods: A decision analytic model incorporating Markov process was developed to compare the cost-effectiveness of gastric bypass, sleeve gastrectomy, and adjustable gastric banding against conventional medical management (CMM). In the model, patients could undergo surgery, or experience post-surgery complications, type 2 diabetes, cardiovascular diseases, or die. Transition probabilities, costs, and utilities were derived from the literature. The impact of different surgical methods on body mass index (BMI) level in the base-case analysis was informed by the Scandinavian Obesity Surgery Registry and the Swedish Obese Subject (SOS) study. Healthcare resource use and costs were obtained from Belgian sources. A base-case analysis was performed for the population, the characteristics of which were obtained from surgery candidates in Belgium. Results: In the base-case analysis over a 10-year time horizon, the increment in quality-adjusted life-years (QALYs) gained from bariatric surgery vs CMM was 1.4 per patient, whereas the incremental cost was €3, 788, leading to an incremental cost-effectiveness ratio (ICER) of €2, 809 per QALY. Over a lifetime, bariatric surgery produced savings of €9, 332, an additional 1.1 life years and 5.0 QALYs. Bariatric surgery was cost-effective at 10 years post-surgery and dominant over conventional management over a lifetime horizon. Limitations: The model did not include the whole scope of obesity-related complications, and also did not account for variation in surgery outcomes for different populations of diabetic patients. Also, the data about management of patients after surgery was based on assumptions and the opinion of a clinical expert. Conclusions: It was demonstrated that a current mix of bariatric surgery methods was cost-effective at 10 years post-surgery and cost-saving over the lifetime of the Belgian patient cohort considered in this analysis.